2015
DOI: 10.1186/s13102-015-0002-0
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of muscular injury repair in a mouse model of notexin-induced lesion with EPI® technique

Abstract: BackgroundThe mechanisms of muscle injury repair after EPI® technique, a treatment based on electrical stimulation, have not been described. This study determines whether EPI® therapy could improve muscle damage.MethodsTwenty-four rats were divided into a control group, Notexin group (7 and 14 days) and a Notexin + EPI group. To induce muscle injury, Notexin was injected in the quadriceps of the left extremity of rats. Pro-inflammatory interleukin 1-beta (IL-1beta) and tumoral necrosis factor-alpha (TNF-alpha)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…This, in turn, results in an increase of the expression of vascular endothelial growth factor (VEGF) and vascular endothelial growth factor receptor 2 (VEGFR-2), mediators responsible for angiogenesis anti-inflammatory response. The EPI ® technique makes for the activation of molecular and cellular mechanisms of the tendon responsible for phagocytosis and the regeneration of degenerated tissue [33,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, results in an increase of the expression of vascular endothelial growth factor (VEGF) and vascular endothelial growth factor receptor 2 (VEGFR-2), mediators responsible for angiogenesis anti-inflammatory response. The EPI ® technique makes for the activation of molecular and cellular mechanisms of the tendon responsible for phagocytosis and the regeneration of degenerated tissue [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a controlled local inflammatory reaction that leads to the regeneration of damaged tissue [33,36].…”
Section: The Application Of Epimentioning
confidence: 99%
“…The application of ultrasound-guided EPI® technique produces a non-thermal electrochemical reaction centered on degenerated tissue (tendinosis). This leads to a controlled local inflammatory reaction that leads to the regeneration of damaged tissue [48,51].…”
Section: Epi® Techniquementioning
confidence: 99%
“…DN consists of the insertion of a needle (filiform and solid, non-bevelled) with the aim of provoking a local injury leading to an inflammatory response and the subsequent regeneration of the injured area in approximately 1 week. A study performed by Abat et al reported that DN induced histological and mechanical changes in rat Achilles tendons at week 1, with changes persisting at week 4 18. Percutaneous needle electrolysis (PNE) is an ultrasound-guided technique used by physiotherapists consisting of causing localised lysis in the damaged and/or degenerated tissue by means of a galvanic current transmitted through an acupuncture needle.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous needle electrolysis (PNE) is an ultrasound-guided technique used by physiotherapists consisting of causing localised lysis in the damaged and/or degenerated tissue by means of a galvanic current transmitted through an acupuncture needle. This technique may affect inflammatory mediators in damaged muscle tissue and influence the new vascularisation of the injured area in rats 18. James et al 11 carried out a cohort study in humans analysing one group treated with DN and another treated with autologous blood injections.…”
Section: Introductionmentioning
confidence: 99%